Research progress of Auricularia heimuer on cultivation physiology and molecular biology - Sun, Xin; Yang, Chunhui; Ma, Yinpeng; Zhang, Jiechi; Wang, Lei (Frontiers in Microbiology, 2022)
A. heimuer(Auricularia heimuer F. Wu, B.K. Cui, Y.C. Dai), a well-known gelatinous fungus used for both food and medicine, is a major edible fungus with a more than 1000-year history of cultivation in China. The nutrients of A. heimuer are abundant, including polysaccharides, melanin, mineral elements, etc. The A. heimuer polysaccharides exhibit antioxidant, immunomodulatory, and anticancer properties. A. heimuer is a completely different species grown in China, unlike Auricularia auricula-judae(Bull.) Quel, which was used to characterize it. The cultivated strain varies based on the local climatic factors and cultivation practices. Hardwood chips are the primary material utilized in the cultivation of substitute materials, which is the principal cultivation technique. However, in actual production, straw is frequently replaced for some wood chips to address the issue of a lack of wood. There are three different types of growing techniques: open-air ground cultivation, arch cultivation, and shed-type hanging substitute cultivation of these three, the quality of A. heimuer grown in a shed is superior to that grown in an open-air environment. The A. heimuer genome sequencing project started later than expected, and the entire genome sequencing was not finished until 2019. A. heimuer's molecular biology studies have mostly concentrated on analyzing genetic diversity and identifying cultivars using molecular markers including RAPD, ISSR, and ITS. There have only been a small number of studies on the function of A. heimuer genes, which have only focused on the preliminary cloning and expression study of a few genes, including the laccase gene and the triterpene compound production gene, among others. However, there is still a lack of comprehensive information concerning A. heimuer, necessitating a synopsis. To our knowledge, this is the first published review of A. heimuer, and it summarizes the most recent studies on its molecular biology and cultivation. This review can serve as a guide for future research on the fungus.